2013
DOI: 10.1002/jgm.2698
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy clinical trials worldwide to 2012 – an update

Abstract: To date, over 1800 gene therapy clinical trials have been completed, are ongoing or have been approved worldwide. Our database brings together global information on gene therapy clinical trials from official agency sources, published literature, conference presentations and posters kindly provided to us by individual investigators or trial sponsors. This review presents our analysis of clinical trials that, to the best of our knowledge, have been or are being performed worldwide. As of our June 2012 update, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
525
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,129 publications
(536 citation statements)
references
References 71 publications
2
525
1
8
Order By: Relevance
“…N onviral gene therapy vectors are of great importance, and they are used in 18% of the total number of clinical trials (Edelstein et al, 2007;Schleef et al, 2010;Ginn, 2013). This is because of their intrinsic biosafety characteristics and many technological improvements, which made nonviral vectors a promising alternative over viral vectors in gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…N onviral gene therapy vectors are of great importance, and they are used in 18% of the total number of clinical trials (Edelstein et al, 2007;Schleef et al, 2010;Ginn, 2013). This is because of their intrinsic biosafety characteristics and many technological improvements, which made nonviral vectors a promising alternative over viral vectors in gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that rAAV1 vectors transduce skeletal muscle more efficiently than rAAV2 vectors, and do not elicit a humoral immune response to the transgene protein (Chao et al, 2001;Mah et al, 2007). Currently, more than 90 clinical trials have begun using rAAV vectors (Ginn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, viral vectors such as adenovirus, retrovirus, vaccinia virus and adeno-associated viruses have accounted for more than 65 % of the clinical trials, mainly because transfection activities using such viral vectors are typically higher than that of non-viral ones [77]. To understand the crucial rate-limiting step in the transfection efficacy in non-viral vectors, we previously compared intracellular trafficking between adenovirus and Lipofectamine Plus ® (lipoplex), as typical viral and non-viral gene carriers [78,79].…”
Section: Lipid Nanoparticles Prepared With Ph-activated and Ss-cleavamentioning
confidence: 99%